2017
DOI: 10.1113/ep086188
|View full text |Cite
|
Sign up to set email alerts
|

Simulated microgravity decreases circulating iron in rats: role of inflammation‐induced hepcidin upregulation

Abstract: What is the central question of this study? Although microgravity is well known to reduce circulating iron in astronauts, the underlying mechanism is still unknown. We investigated whether hepcidin, a key hormone regulating iron metabolism, could be involved in this deleterious effect. What is the main finding and its importance? We show that hindlimb suspension, a model of microgravity, stimulates the production of hepcidin in liver of rats. In agreement with the biological role of hepcidin, we found a decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 35 publications
5
29
0
4
Order By: Relevance
“…Iron deposition in the liver and spleen was significantly increased in mice after unloading for 28 days [ 18 , 44 ]. An increase of the spleen iron content also was found in a study of 7-day HLU rats [ 45 ]. Systemic iron metabolism is mainly controlled by hepcidin, a hormone produced by the liver.…”
Section: The Effect Of Spaceflight Environment and Its Analogs On mentioning
confidence: 59%
See 1 more Smart Citation
“…Iron deposition in the liver and spleen was significantly increased in mice after unloading for 28 days [ 18 , 44 ]. An increase of the spleen iron content also was found in a study of 7-day HLU rats [ 45 ]. Systemic iron metabolism is mainly controlled by hepcidin, a hormone produced by the liver.…”
Section: The Effect Of Spaceflight Environment and Its Analogs On mentioning
confidence: 59%
“…Under inflammatory conditions, interleukin-6 (IL-6) and relevant cytokines bind to the IL-6 receptor, leading to the activation of signal transducer and activator of transcription 3 (STAT3), which in turn promotes hepcidin production [ 6 ]. After HLU for seven days, the mRNA levels of hepcidin were enhanced in the liver of rats, accompanied by the activation of the IL-6/STAT3 axis [ 45 ]. Therefore, these data imply that the changes in iron metabolism may be mediated through upregulating hepcidin via an inflammatory process in microgravity.…”
Section: The Effect Of Spaceflight Environment and Its Analogs On mentioning
confidence: 99%
“…8 Interestingly, hepatic hepcidin expression and blood hepcidin levels increase in rodents exposed to simulated microgravity. [8][9][10] As hepcidin controls iron release from cells, especially spleen macrophages, it could play a key role in microgravity-induced iron misdistribution by limiting the expression and activity of ferroportin, the cell iron exporter that allows iron recycling from macrophages in plasma. 11 Notably, it has been suggested that iron metabolism has strong interactions with other essential metals, especially due to the fact that some iron proteins could also participate in the metabolism of other metals.…”
Section: Introductionmentioning
confidence: 99%
“…On the ground, mechanical unloading‐induced bone loss in mice was connected with iron overload . In rats, a decrease in the levels of circulating iron and an increase in iron content of the spleen was found after unloading for 14 days . Interestingly, we have found that HyMF aggravated the increase of body iron storage induced by HLU in mice .…”
Section: Introductionmentioning
confidence: 77%